Suppression of cell wall-related genes associated with stunting of Oryza glaberrima infected with Rice tungro spherical virus - Budot, Bernard O.; Encabo, Jaymee R.; Ambita, Israel Dave V.; Atienza-Grande, Genelou A.; Satoh, Kouji; Kondoh, Hiroaki; Ulat, Victor J.; Mauleon, Ramil; Kikuchi, Shoshi; Choi, Il-Ryong (Frontiers in Microbiology, 2014)
Rice tungro disease is a complex disease caused by the interaction between Rice tungro bacilliform virus and Rice tungro spherical virus (RTSV). RTSV alone does not cause recognizable symptoms in most Asian rice (Oryza sativa) plants, whereas some African rice (O. glaberrima) plants were found to become stunted by RTSV. Stunting of rice plants by virus infections usually accompanies the suppression of various cell wall-related genes. The expression of cell wall-related genes was examined in O. glaberrima and O. sativa infected with RTSV to see the relationship between the severity of stunting and the suppression of cell wall-related genes by RTSV. The heights of four accessions of O. glaberrima were found to decline by 14 to 34% at 28 days post-inoculation (dpi) with RTSV, whereas the height reduction of O. sativa plants by RTSV was not significant. RTSV accumulated more in O. glaberrima plants than in O. sativa plants, but the level of RTSV accumulation was not correlated with the degree of height reduction among the four accessions of O. glaberrima. Examination for expression of genes for cellulose synthase A5 (CESA5) and A6 (CESA6), cellulose synthase-like A9 (CSLA9) and C7, and -expansin 1 (expansin 1) and 15 precursors in O. glaberrima and O. sativa plants between 7 and 28 dpi with RTSV showed that the genes such as those for CESA5, CESA6, CSLA9, and expansin 1were more significantly suppressed in stunted plants of O. glaberrima at 14 dpi with RTSV than in O. sativa, suggesting that stunting of O. glaberrima might be associated with these cell wall-related genes suppressed by RTSV. Examination for expression of these genes in O. sativa plants infected with other rice viruses in previous studies indicated that the suppression of the expansin 1 gene is likely to be a signature response commonly associated with virus-induced stunting of Oryza species. These results suggest that stunting of O. glaberrima by RTSV infection might be associated with the suppression o